2007
DOI: 10.1002/app.26175
|View full text |Cite
|
Sign up to set email alerts
|

Soy protein plastics reinforced and toughened by SiO2 nanoparticles

Abstract: The nano-SiO 2 particles were compounded into soy protein isolated (SPI) matrix to produce a series of reinforcing nanocomposite sheets by compression-molding. Except for the expected increase of strength and modulus, the elongation was also enhanced when the nano-SiO 2 content was lower than 8 wt %. Moreover, two nanocomposite materials were recommended: the one is a nanocomposite containing 4 wt % nano-SiO 2 with the highest strength and enhanced elongation, the other is a reinforced material with the best e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 23 publications
4
29
0
Order By: Relevance
“…The resultant viscous solution (dark-gray for the REC/PPI blends and light-yellow for the MMT/PPI blends) was freeze-dried for 48 h to obtain the nanocomposites (gray REC/PPI powder or yellow MMT/PPI powder), which preserved the original complex state in solution. According to the REC content in solid powders of 2,4,8,12,16,20, and 24 wt %, the gray nanocomposite powders were coded as RP-2-P, RP-4-P, RP-8-P, RP-12-P, RP-16-P, RP-20-P, and RP-24-P, respectively. Meanwhile, the yellow nanocomposite powders containing 2,4,8,12,16,20, and 24 wt % MMT were coded as MP-2-P, MP-4-P, MP-8-P, MP-12-P, MP-16-P, MP-20-P, and MP-24-P, respectively.…”
Section: Experimental Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resultant viscous solution (dark-gray for the REC/PPI blends and light-yellow for the MMT/PPI blends) was freeze-dried for 48 h to obtain the nanocomposites (gray REC/PPI powder or yellow MMT/PPI powder), which preserved the original complex state in solution. According to the REC content in solid powders of 2,4,8,12,16,20, and 24 wt %, the gray nanocomposite powders were coded as RP-2-P, RP-4-P, RP-8-P, RP-12-P, RP-16-P, RP-20-P, and RP-24-P, respectively. Meanwhile, the yellow nanocomposite powders containing 2,4,8,12,16,20, and 24 wt % MMT were coded as MP-2-P, MP-4-P, MP-8-P, MP-12-P, MP-16-P, MP-20-P, and MP-24-P, respectively.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…5 The exfoliated lamella of layered silicates strongly adhered onto the soy protein matrix by electrostatic affiliating as well as hydrogen bonding to produce reinforced materials. 6,7 The nano-clusters of aggregated spherical SiO 2 nanoparticles 8 and flexible carbon nanotubes 9 played a role on reinforcing and toughening soy protein plastics simultaneously. Meanwhile, the biodegradable polysaccharide nanoparticles, such as rod-like cellulose 10 and chitin 11 whiskers, and platelet-like starch nanocrystal, 12 were used to reinforce soy protein as well as enhancing water resistance.…”
Section: Introductionmentioning
confidence: 99%
“…This could be attributed to chain cross‐linking, which established hydrogen bonds and coordination bonds between the nano‐SiO 2 and SPI. Thus, more compact film structures were formed when the nano‐SiO 2 addition increased so that the diffusion of the water vapor and oxygen were disturbed (Ai, Zheng, Wei, & Huang, ; Bai, Xu, Liao, & Liu, ). Tunç, Duman, and Polat () came to similar conclusions, namely, that the montmorillonite nanocomposite could decrease the WVP in methyl cellulose films.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been explored the use of rectorite, a clay mineral consisting of regular interstratification of montmorillonite-type and mica-type layers, as filler, being also observed that the bionanocomposite with a 12 wt% clay loading shows the highest strength [68]. The use of rigid nanoparticles of SiO 2 produces a kind of reinforced and toughened bionanocomposite however the amount of nanofiller must be controlled as separation of SPI microphases and SiO 2 domains has been observed [70]. More interesting seems to be the use of MWCNTs that with just a 0.25 wt% content results in reinforced and thoughened SPI bionanocomposites provided also of higher water resistance.…”
Section: Bionanocomposites For Bioplasticsmentioning
confidence: 97%
“…Soybean protein isolate (SPI) extracted from soybean contains more than 90% of proteins (mainly glycinin and β-conglycinin) and attracts increasing interest because it can be thermoplastically processed by using plasticizer small molecules, such as glycerol. The incorporation of different type of fillers, including polyphosphates [64], different type of clays [65][66][67][68], talc powders and zeolites [65], carbon nanotubes [69] or SiO 2 nanoparticles [70] have been tested to improve its film properties. The use of clays introduces improvement of the tensile strength decreasing water vapor permeability and water solubility but also elongation at break in the biocomposites [65].…”
Section: Bionanocomposites For Bioplasticsmentioning
confidence: 99%